The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1161/jaha.120.017455
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Myocardial Bridge on Life‐Threatening Ventricular Arrhythmia in Patients With Implantable Cardioverter Defibrillator

Abstract: Background Myocardial bridge (MB), common anatomic variant, is generally considered benign, while previous studies have shown associations between MB and various cardiovascular pathologies. This study aimed to investigate for the first time possible impact of MB on long‐term outcomes in patients with implantable cardioverter defibrillator, focusing on life‐threatening ventricular arrhythmia (LTVA). Methods and Results This retrospective a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The results of the cited study must be discounted because the patients in this study were a group of patients who underwent CFT for suspected coronary spasm and were actually diagnosed with VSA in 63% of the studied patients. Nevertheless, 87% of patients with MB had provoked coronary spasms, which fully confirms the results of previous studies showing an increased susceptibility to coronary spasms in patients with MB [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Regarding the relationship between coronary spasms and MB, Im et al [ 13 ] showed that coronary spasms in patients with MB was provoked at a low ACh dose, and the spasms were severe, diffuse and long.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The results of the cited study must be discounted because the patients in this study were a group of patients who underwent CFT for suspected coronary spasm and were actually diagnosed with VSA in 63% of the studied patients. Nevertheless, 87% of patients with MB had provoked coronary spasms, which fully confirms the results of previous studies showing an increased susceptibility to coronary spasms in patients with MB [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Regarding the relationship between coronary spasms and MB, Im et al [ 13 ] showed that coronary spasms in patients with MB was provoked at a low ACh dose, and the spasms were severe, diffuse and long.…”
Section: Discussionsupporting
confidence: 88%
“…Because of the combination of the presence of atherosclerosis beneath the MB and systolic compression of the coronary artery by MB, it has been reported that FFR is reduced in patients with MB [ 1 ]. Third, MB may increase the susceptibility to coronary spasms [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They revealed that patients with MB had significantly higher rates of LTVA and a higher prevalence of vasospastic angina than patients without MB. It may account for some potential mechanisms for bad prognosis in patients with myocardial infarction/ischemia with non-obstructive coronary arteries (MINOCAs) (41). MB may be the major etiology of angina in MINOCA, given the high proportion (58%) of patients with MB detected by IVUS in patients suffering from angina but without the absence of obstructive CAD (42).…”
Section: Discussionmentioning
confidence: 99%
“…MB may be the major etiology of angina in MINOCA, given the high proportion (58%) of patients with MB detected by IVUS in patients suffering from angina but without the absence of obstructive CAD (42). Although most MBs were considered a benign cardiovascular anomaly, the potential poor prognosis of some symptomatic patients should be paid more attention, and the evaluation of MB seems to improve the identification of high-risk individuals in case of the occurrence of LTVA or sudden death (41).…”
Section: Discussionmentioning
confidence: 99%